PENDUGAAN POTENSI AIR TANAH BESERTA KEDALAMAMNYA DENGAN METODE RESISTIVITAS KONFIGURASI SHLUMBERGER DI NGLANGGERAN KULON KABUPATEN GUNUNG KIDUL - Dzakiyah Nurul; Subhan Arif; Radhitya Adzan Hidayah; Dewa Gede Eka Setiawan (Jambura Physics Journal, 2022)
Research on the estimation of groundwater potential and its depth has been carried out in Nglanggeran Kulon which is the Nglanggeran Ancient Volcano Tourism Village in Gunung Kidul. The large number of tourists who visit makes the need for groundwater in this location also increases but has not been matched by its availability. This area is also a district that almost every dry season experiences a water crisis. The purpose of this study was to find out the potential presence of groundwater and its depth. This is related to the efforts of local residents who want to build new wells. The method used is the geoelectric resistivity method with the Shlumberger configuration. This method exploits the electrical properties of the rock beneath the surface. The physical parameter measured is the resistivity value to create a subsurface geological model in the form of a 1D model. The length of the stretch carried out is 125 m at two measurement points. The results of this study indicate that 1st point has two layers of rock and no groundwater potential is found. 2nd point has four layers of rock. Groundwater potential is found in 2nd layer because it has a low resistivity value of 9.89 ꭥm at depths ranging from 5-9 meters with a thickness of about 4 meters. So that the location of the 2nd point is more recommended for making new wells.